DESIGNATION OF GENDER ON ELECTRONIC EFL TEXTBOOK FOR SENIOR HIGH SCHOOL - Imam Santosa (Indonesian EFL Journal, 2020)
This study aims to examine gender representation in the electronic EFL textbook for senior high school. Content analysis will be utilized to examine gender representation in the electronic EFL textbook for senior high school entitles â€œBahasa Inggris Xâ€ published by Puskurbuk. The study probes gender representation focusing on the designation of the character proposed by UNESCO. The designation of the gender representation in the textbook comprises 5 designations; first name, family relationship, other relationship, occupational status (agriculture, education, trade, small business, health, art and culture, and office) other status. The study later will reveal how the designation of the gender representation in the textbook. The comparison is 40% and 31%. Unsurprisingly, the number considered as ungendered character is slightly lower in 29. The designation of the character in textbook is dominated by first name with 98 appearance for male and 82 for female character. Then, the category followed by occupation status, (68:60 character), other relationship (52:34), and family relationship category (34:20). The result concluded that male character dominated in all designation category strengthen the position of the male as dominant character. Additionally, the result of the study will give the insight on how gender representation exists as the basis to evaluate the construction of the textbook.Keywords: gender; gender bias; gender representation; textbook.